2017
DOI: 10.1186/s12913-017-2063-0
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension management in rural primary care facilities in Zambia: a mixed methods study

Abstract: BackgroundImproved primary health care is needed in developing countries to effectively manage the growing burden of hypertension. Our objective was to evaluate hypertension management in Zambian rural primary care clinics using process and outcome indicators to assess the screening, monitoring, treatment and control of high blood pressure.MethodsBetter Health Outcomes through Mentoring and Assessment (BHOMA) is a 5-year, randomized stepped-wedge trial of improved clinical service delivery underway in 46 rural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 25 publications
3
33
0
3
Order By: Relevance
“…Consistent with other African data [17], only half of patients were aware of having HBP, and similar to our study at rural outpatient clinics in Zambia [18], few patients took anti-hypertensive drugs. Challenges to HIV-NCD integration range from low patient and provider awareness, education, and training to structural and logistic barriers [7,19]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with other African data [17], only half of patients were aware of having HBP, and similar to our study at rural outpatient clinics in Zambia [18], few patients took anti-hypertensive drugs. Challenges to HIV-NCD integration range from low patient and provider awareness, education, and training to structural and logistic barriers [7,19]. …”
Section: Discussionmentioning
confidence: 99%
“…CVD-related mortality is anticipated to increase as HIV-infected patients initiate antiretroviral therapy (ART) at CD4+ counts >200 and opportunistic infections become uncommon [35]. In sub-Saharan Africa, there are numerous challenges in the diagnosis and control of hypertension (HTN), including low awareness among patients and providers [6], overcrowded clinics, and limited opportunities for HTN screening [7]. Care and treatment programs for HIV present a promising platform to address HTN because care is provided longitudinally, and most clinics provide pharmacy, laboratory, and clinical services as well as counseling and health education [8].…”
Section: Introductionmentioning
confidence: 99%
“…But the rate of change does not increase. BHOMA system applies some of the programs that are also applied in Prolanis 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Mainly cardiovascular diseases, diabetes, chronic lung disease and cancers, account for 86 % of premature deaths in LMICs . Often there is an absence of even basic functional diagnostic equipment . In Mozambique, for example it is reported that only 6 % of facilities could carry out a basic blood glucose analysis and personal monitoring is not available in general .…”
Section: Introductionmentioning
confidence: 99%